Crack initiation characteristics of ring chain of heavy-duty scraper conveyor under time-varying loads - Dagang Wang (Advances in Mechanical Engineering, 2019)
Crack initiation characteristics of ring chain of heavy-duty scraper conveyor under time-varying loads were investigated in this study. The dynamic tension of ring chain of the heavy-duty scraper conveyor was obtained using the time-varying dynamic analysis. Finite element analyses of three-dimensional contacts between adjacent chain rings at straight and bending segments were carried out to explore three-dimensional stress distributions of chain rings. The crack initiation life of chain ring was predicted employing the multiaxial fatigue theory. The results show that the ring chain is subjected to time-varying dynamic tensions during operation. During tension-tension contact fatigue, as compared to the straight segment of ring chain, the bending segment engaging in the sprocket presents an overall lower (or higher) equivalent stress distribution in the case of flat (or vertical) chain ring, respectively. Maximum equivalent stresses at the contact regions of adjacent chain rings both present time-varying dynamic characteristics similar to evolutions of dynamic tension. During tension-torsion contact fatigue, an increase in torsion angle level causes unobvious difference between equivalent stress distributions at contact regions of adjacent rings. Predicted crack initiation lives of chain rings during tension-tension contact fatigue indicates more severe fatigue damages of the vertical chain ring at the straight segment and of the flat chain ring at the right bending segment.